BF3·OEt2-Catalyzed Synthesis of anti-β-(N-Arylamino)-α-hydroxynitriles by Regio- and Diastereospecific Ring Opening of 3-Aryloxirane-2-carbonitriles with Anilines - Xu, Chuangchuang; Lu, Yang; Xu, Kaini; Xu, Jiaxi (Synthesis, 2020)
A safe and convenient synthetic method to anti-β-(N-arylamino)-α-hydroxynitriles from 3-aryloxirane-2-carbonitriles and anilines was developed under the catalysis of BF3·OEt2 in ethanol. In this method, BF3·OEt2 first reacts with ethanol to produce the true catalyst of super acid H[B(OEt)F3], followed by an acid-catalyzed regio- and diastereospecific ring opening of oxirane-2-carbonitriles with anilines, generating anti-β-(N-arylamino)-α-hydroxynitriles. The method features the advantages of non-metal catalysis, short reaction times, and easy operation, and uses an environmentally friendly solvent.
Keywords: amino-hydroxynitrile; boron trifluoride; ring opening; regiospecificity; diastereospecificity; oxiranecarbonitrile; aniline